Ursolic Acid Ameliorates Spinal Cord Injury in Mice by Regulating Gut Microbiota and Metabolic Changes - Rong, Zi-Jie; Cai, Hong-Hua; Wang, Hao; Liu, Gui-Hua; Zhang, Zhi-Wen; Chen, Min; Huang, Yu-Liang (Frontiers in Cellular Neuroscience, 2022)
Background: Spinal cord injury (SCI) damages the autonomic nervous system and affects the homeostasis of gut microbiota. Ursolic acid (UA) is a candidate drug for treating nervous system injury due to its neuroprotective and antioxidant functions. The purpose of our study was to investigate the role of UA on SCI and its mechanism. Methods: UA was administered to SCI mice and the solvent corn oil was used as control. The weight of the mice was recorded daily. Mice feces were collected in 21 days after surgery for 16S rRNA-amplicon sequencing and untargeted metabolomics analysis. The expressions of NF-κB, IL-1β and TNF-α in the spinal cord and colon tissues of mice were detected by Western blot and Enzyme-linked immunosorbent assay, respectively. Immunohistochemistry was used to analyze the expression of NeuN, NF-200, and Synapsin in the spinal cord tissues. Results: UA treatment increased body weight and soleus muscle weight of SCI mice. UA treatment inhibited inflammatory response and protected neuronal activity in SCI mice. UA improved the relative abundance of Muribaculaceae, Lachnospiraceae_NK4A136_group, and Alloprevotell genus in the gut tract of SCI mice. SCI destroyed the Glutamine_and_D-glutamate_metabolism, Nitrogen_metabolism, Aminoacyl-tRNA_biosynthesis, and Taurine_and_hypotaurine_metabolism in the gut of mice, which might be alleviated by UA. Conclusions: UA treatment could inhibit SCI progression by improving the gut environment and metabolic changes, promoting synaptic regeneration and anti-inflammatory effects.